Automatic Text Summarization Methods: A Comprehensive Review - Sharma, Grishma; Sharma, Deepak (SN computer science, 2023)
Text summarization is the process of condensing a long text into a shorter version by maintaining the key information and its meaning. Automatic text summarization can save time and helps in selecting the important and relevant sentences from the document. In extractive summarization techniques, sentences are picked up directly from the source document, whereas in abstractive summarization techniques, new sentences and phrases are generated from original source document. Majority of research is focused on extractive techniques, in the recent years, most of the research is inclined towards abstractive & hybrid text summarization methods. This paper presents comprehensive survey on various works performed for automatic text summarization methods. Detailed study is done on the Extractive & Abstractive techniques & their comparison on different aspects. The paper also discusses the research gaps & challenges that can motivate & help researchers to identify the potential areas for research in this field.